Training in Local Food Calorific Value Analysis Using Environment-Based Learning Media to Improve Students’ Scientific Literacy and Numeracy at SMAK Sint. Carolus, Kupang (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Indonesian students’ science literacy and numeracy skills remain relatively low a condition linked to rote-oriented instruction and a shortage of contextual learning materials. The Kupang region, however, holds abundant local food resources that can serve as authentic learning material. This community service activity trained one teacher and fifteen students of SMAK Sint. Carolus, Kota Kupang, in environment-based media centered on caloric value analysis of local food. The program ran weekly on Fridays from April to early May 2026 at the partner school and the Physics Laboratory of FKIP Universitas Katolik Widya Mandira Kupang, following seven stages: preparation, media design, pretest, implementation, posttest and evaluation, data analysis, and follow-up planning. Data were collected with a nine-item literacy-numeracy test built around the caloric value of coconut, candlenut, and peanut, then analyzed using the N-gain equation and a paired-samples t-test. The average score rose from the low category of 37.4 on the pretest to the very good category of 91.8 on the posttest, a difference confirmed by a paired t-test, t (14) = 13.67, p < .001, with an N-gain of 0.87 in the high category. Beyond this quantitative gain, the activity strengthened students’ critical thinking, data evaluation, and mathematical reasoning skills, and left the partner teacher with a reusable calorimetry-based instructional model that connects local wisdom to the science curriculum.